Blockchain Based Compliance Auditing For GRC Integration in Hybrid Cloud IT Governance Frameworks - Ugoaghalam Uche James, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The integration of blockchain technology into compliance auditing presents a transformative opportunity for enhancing Governance, Risk, and Compliance (GRC) mechanisms within hybrid cloud IT governance frameworks. This review explores the potential of blockchain to address long-standing challenges in auditability, transparency, and trust across distributed and heterogeneous computing environments. By leveraging blockchain’s immutable ledger, smart contract automation, and decentralized consensus protocols, organizations can ensure real-time verification of compliance activities, secure audit trails, and enforceable policy adherence across cloud infrastructures. The paper critically evaluates existing literature on blockchain-enabled compliance auditing, identifies gaps in current GRC integration practices within hybrid cloud ecosystems, and discusses emerging frameworks that align regulatory compliance with dynamic IT operations. Key challenges such as interoperability, scalability, and regulatory acceptance are analyzed alongside opportunities for enhanced accountability, cross-border compliance, and audit automation. The review concludes by outlining future research directions, emphasizing the need for standardized blockchain-GRC interfaces, regulatory sandboxing, and industry-specific implementation models to fully realize the benefits of blockchain in hybrid cloud IT governance.
Keywords: Cross-Border Compliance; Regulatory Automation; International Standards; Collaborative Governance; Smart Contracts; Digital Policy Integration